Attitude control of apricot during orientation transmission - Xiangyan, Ding; Chunyao, Wang; Chunyang, Huang; Jianqing, Luo (International Journal of Agricultural and Biological Engineering, 2016)
The kinetic characteristics of apricots during orientation transmission were studied to provide a basis for improving the structure of the transmission device. Previous studies have generally focused on the development of orientation devices, but few studies have been conducted to analyze the mechanisms of orientation. In order to study the attitude control in the orientation mechanisms, an orthogonal combination test was performed and a rigid kinetic model for a monosymmetric apricot was developed based on Euler’s kinetic equations with the modified Rodrigue parameters (MRPs). Kinetic simulation and analysis based upon the attitude control law were conducted and an attitude control simulation platform was created. The simulation results showed that the orientation transmission system for monosymmetric apricots was globally convergent and tended to stable. The experimental torques also affected the orientation success rates. The calculated average experimental torque value (0.164 N•m) was consistent with the maximum control torque value (0.16478 N•m) when the system was in a stable state in Simulink. The consistency between the simulation result and the calculated control torque validates the correctness of the designed control torques.Keywords: attitude control, apricot, orientation transmission, torque control, monosymmetric fruitDOI: 10.3965/j.ijabe.20160905.2135Citation: Ding X Y, Wang C Y, Huang C Y, Luo J Q. Attitude control of apricot during orientation transmission. Int J Agric & Biol Eng, 2016; 9(5): 9-16.